MIR137HG risk variant rs1625579 genotype is related to corpus callosum volume in schizophrenia. (18th August 2015) - Patel, Veena S.; Kelly, Sinead; Wright, Carrie; Gupta, Cota Navin; Arias-Vasquez, Alejandro; Perrone-Bizzozero, Nora; Ehrlich, Stefan; Wang, Lei; Bustillo, Juan R.; Morris, Derek; Corvin, Aiden; Cannon, Dara M.; et al.
Highlights: We examine how the microRNA-137-associated variant rs1625579 affects subcortical volumes in schizophrenia. In patients, the homozygous risk genotype confers lesser reduction of callosal volume. Results are robust after considering possible multi-site and ethnicity confounds. Results suggest variant does not mediate schizophrenia risk through corpus callosum volume reduction. Abstract: Genome-wide association studies implicate the MIR137HG risk variant rs1625579 (MIR137HGrv) within the host gene for microRNA-137 as a potential regulator of schizophrenia susceptibility. We examined the influence of MIR137HGrv genotype on 17 subcortical and callosal volumes in a large sample of individuals with schizophrenia and healthy controls ( n  = 841). Although the volumes were overall reduced relative to healthy controls, for individuals with schizophrenia the homozygous MIR137HGrv risk genotype was associated with attenuated reduction of mid-posterior corpus callosum volume ( p  = 0.001), along with trend-level effects in the adjacent central and posterior corpus callosum. These findings are unique in the literature and remain robust after analysis in ethnically homogenous and single-scanner subsets of the larger sample. Thus, our study suggests that the mechanisms whereby MIR137HGrv works to increase schizophrenia risk are not those that generate the corpus callosum volume reductions commonly found in the disorder.